The Analysis Of Process Costing Method: A Case Study In Ultra Micro Business - Rohma, Frida Fanani; Elviana Andrian Nova Wahyu, Prasiwi (Unversitas Islam Madura, 2022)
The process costing is a crucial factor in assigning production costs to the manufacturing business. Some of the realities that are a problem, especially the micro industry, are the less accurate calculation of process costing methods. This causes the determination of the cost of goods sold to be uncertain which can have an impact on the quality of earnings. The research uses a qualitative method with a case study approach on micro-enterprises that produce Shuttlecocks. This study specifically analyzes the use of the process costing method in determining the cost of production. The results of the analysis show that the Shuttlecocks micro business still makes mistakes in allocating the costs incurred. Owned resource capacity is the main problem of inaccuracy of loading. This has an impact on the component of factory overhead costs to be accurate. Thus, the potential for error in costing and cost control efforts cannot run optimally which can have an impact on long-term profit for the business